1998
DOI: 10.1103/physrevlett.81.2930
|View full text |Cite
|
Sign up to set email alerts
|

First Stage of Oxygen Aggregation in Silicon: The Oxygen Dimer

Abstract: The structure and dynamic properties of the interstitial oxygen dimer in silicon are found using a combination of infrared spectroscopy and ab initio modeling. We find that the stable dimer consists of a pair of inequivalent weakly coupled interstitial oxygen atoms separated by a Si-Si bond. Two high frequency modes are decoupled in one 16 O-18 O combination but are strongly mixed in the other combination. A third lower lying mode involves the compression of the Si-Si bond joining the oxygen atoms and gives di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 17 publications
3
29
1
Order By: Relevance
“…And, since the symmetric stretching vibration of O i has not been detected because either a linear Si-O i -Si "molecule" is infrared inactive [24] or the amplitude of O i in a puckered case is anyway small [21], it is natural that the symmetric stretching modes of the skewed O i -Si-Si-O i configuration are not detected either. The absence of only the lower frequency of the symmetric stretching frequency pair of the staggered configuration (Table I) Öberg et al [9] using an H-terminated cluster of 88 atoms (44 Si atoms) reported that their calculated frequencies for the skewed O i -Si-Si-O i configuration correlate quite well with the four experimental frequencies while those for their configuration (i)-corresponding to the staggered geometry-do not (Table I). Especially the large mixed 18 O !…”
Section: Vibrations Of the Interstitial Oxygen Pairs In Siliconsupporting
confidence: 67%
See 3 more Smart Citations
“…And, since the symmetric stretching vibration of O i has not been detected because either a linear Si-O i -Si "molecule" is infrared inactive [24] or the amplitude of O i in a puckered case is anyway small [21], it is natural that the symmetric stretching modes of the skewed O i -Si-Si-O i configuration are not detected either. The absence of only the lower frequency of the symmetric stretching frequency pair of the staggered configuration (Table I) Öberg et al [9] using an H-terminated cluster of 88 atoms (44 Si atoms) reported that their calculated frequencies for the skewed O i -Si-Si-O i configuration correlate quite well with the four experimental frequencies while those for their configuration (i)-corresponding to the staggered geometry-do not (Table I). Especially the large mixed 18 O !…”
Section: Vibrations Of the Interstitial Oxygen Pairs In Siliconsupporting
confidence: 67%
“…16 O isotopic shift and is characterized as Si related [9]. We find a local oxygen-induced Si mode of this type just above the region of delocalized vibrations Reference [9]. b Reference [8].…”
Section: Vibrations Of the Interstitial Oxygen Pairs In Siliconmentioning
confidence: 85%
See 2 more Smart Citations
“…1͑c͒ found by Ö berg et al 44 47 find a slightly bound O 2i . Ö berg et al 44 find that the skewed O i -Si-Si-O i configuration is by 0.14 eV more stable than an O 2i configuration consisting of two neighboring O i 's bound to a common silicon atom, whereas Ewels et al 48 found earlier using the same method that the latter configuration is more stable by 0.68Ϫ0.82 eV. Thus, considerable differences exist between different calculations.…”
Section: Resultsmentioning
confidence: 80%